Ethylene glycol dry reforming on Ni/Al2O3 catalyst for syngas generation - Bahari, M. B.; Jun, Lau N.; Nor Shafiqah, Mohd Nasir; Fayaz, Fahim; Vo, Dai-Viet N. (IOP Publishing, 2018)
It is the first time ethylene glycol dry reforming (EGDR) reaction was carried out for syngas production on 10%Ni/Al2O3 catalyst in a tubular fixed-bed reactor at atmospheric condition. Wet-impregnation method was employed for the synthesis of 10%Ni/Al2O3 catalyst. The results of X-ray diffraction measurement revealed the presence of γ-Al2O3, NiO, NiAl2O4, Ni0 and graphitic carbon phases on the surface of spent 10%Ni/Al2O3 catalyst. H2 temperature-programmed reduction indicates that NiO and NiAl2O4 phases were totally reduced to metallic nickel phase at reduction temperature above 970 K. EGDR activity appeared to be steady with time-on-stream beyond 5-7 h. Catalytic activity was considerably improved with increasing feed ratio of CO2:C2H6O2 from 1:1 to 2.5:1.